Metal-Ions Intercalation Mechanism in Layered Anode From First-Principles Calculation - Zhang, Junbo; Lu, Xiaodong; Zhang, Jingjing; Li, Han; Huang, Bowen; Chen, Bingbing; Zhou, Jianqiu; Jing, Suming (Frontiers in Chemistry, 2021)
Layered structure (MoS2) has the potential use as an anode in metal-ions (M-ions) batteries. Here, first-principles calculations are used to systematically investigate the diffusion mechanisms and structural changes of MoS2 as anode in lithium (Li)-, sodium (Na)-, magnesium (Mg)- and Zinc (Zn)-ions batteries. Li and Na ions are shown to be stored in the MoS2 anode material due to the strong adsorption energies (~-2.25 eV), in contrast to a relatively weak adsorption of Mg and Zn ions for the pristine MoS2. To rationalize the results, we evaluate the charge transfer from the M-ions to the MoS2 anode, and find a significant hybridization between the adsorbed atoms and S atoms in the MoS2 anode. Furthermore, the migration energy barriers of M ions are explored using first-principles with the climbing image nudged elastic band (CINEB) method, and the migration energy barrier is in the order of Zn > Mg > Li > Na ions. Our results combined with the electrochemical performance experiments show that Li- and Na-ions batteries have good cycle and rate performance due to low ions migration energy barrier and high storage capability. However, the MoS2 anode shows poor electrochemical performance in Zn- and Mg-ions batteries, especially Zn-ion batteries. Further analysis reveals that the MoS2 structure undergoes the phase transformation from 2H to 1T during the intercalation of Li and Na ions, leading to strong interaction between M ions and the anode, and thus higher electrochemical performance, which, however, is difficult to occur in Mg- and Zn-ions batteries. This work focuses on the theoretical aspects of M-ions intercalation, and our findings may stimulate the experimental work for the intercalation of multi-ions to maximize the capacity of anode in M-ions batteries.